Multi-sector partnerships for the public good - Brown, Samuel L. (Social scientist); Johnson, Richard Greggory (Public administration & social equity., 2023)
"What is the way that societies improve and solve problems? What is the purpose of business in society? Is there a role for markets and business in issues of civic good, justice, equality, education, environment, health or collective action? Current economic principles, which underpin our trust in markets are not value neutral. Therefore, how we design "market solutions" to problems should be the focus of vigorous and open debate. Multi-sector Partnership is a concept that has re-focused us on the meaning of the goods and social practices we value as citizens in a global society. Multi-sector partners emerge in society to offer innovative approaches to dealing with pressing, yet complex, social, economic and weather-related 21st century challenges. Multi-sector partnerships, loosely defined as activities with an embedded social purpose, is about using skills from a range of sectors to craft innovative responses to address social problems. It aims at social impact but does not exclude economic wealth creation. Thus, it is not limited to the non-profit or social sectors but seeks to mobilize and align interests of diverse stakeholders in the social, public and private sectors by creating non-financial incentives for collective action. Multi-sector partnerships involve recognizing that social problems are potential opportunities for collaboration, building on existing social networks, harnessing market forces that combine and mobilize resources, inciting positive change in various domains, and designing solutions for sustainable development. The purpose of this edited volume is to provide academic and practitioners with the essential conceptual frameworks and tools for creating successful Multi-sector ventures, initiatives, programs or partnerships that seek to tackle global social issues and collective action problems"--